Computed Tomography Profile and its Utilization in Head Injury Patients in Emergency Department: A Prospective Observational Study - Archana Waganekar; Jagadish Sadasivan; A Sathia Prabhu; K T Harichandrakumar (Journal of Emergencies, Trauma and Shock, 2018)
Context: Based on Glasgow Coma Scale (GCS), head injury can be classified as minor (GCS 13–15), moderate (GCS 9–12), and severe (GCS 3–8). There is a lot of controversy in the use of computed tomography (CT) in head injury patients. Aims: This study was intended to estimate the rate of CT positivity in head injury patients and to define the criteria for doing CT in head injury patients. Settings and Design: This was a prospective observational study in the emergency department (ED) over a 12-month period. Subjects and Methods: Study involved all head injury patients attending ED. Risk factors studied were a loss of consciousness (LOC), vomiting, seizures, ear bleed, nosebleed, external injuries, and alcohol intoxication. Statistical Analysis Used: Comparison of CT positivity with the patient's demographics and clinical characteristics was carried out using Chi-square. Results: A total of 1782 patients were included in this study. Overall CT positivity was 50.9%. In minor head injury (MHI), CT positivity rate was 38%. The study showed significant association of CT positivity with five variables: LOC >5 min, vomiting, seizures, ear bleed, and nosebleed. Conclusions: From the study, we recommend following: CT is indicated in all patients with moderate and severe head injury (GCS ≤12). Low threshold for taking CT is advisable in elderly and alcohol-intoxicated patients. In MHI, CT is indicated if any one of the following risk factors are present: LOC >5 min, history of vomiting, history of seizures, history of ear bleed, and history of nosebleed.